The Effect Of Investment Knowledge, Investment Motivation and Technological Advancements On Student Investment Interest in the Capital Market - Nailal Husna; Masdupi, Erni; Yanuarta, Ramel (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the influence of investment knowledge, investment motivation, and technological advancement on students' investment interest in the capital market. The research involved 116 students from the Faculty of Economics and Business at Bung Hatta University. Data were analyzed using multiple linear regression via Stata 17. The findings show that all three variables significantly and positively affect investment interest. These results imply the importance of enhancing students' financial education and leveraging technological tools to foster early investment behavior. Keywords: Investment Knowledge, Investment Motivation, Technological Advancement, Investment Interest, Capital Market, Student Behavior, Financial Education, Regression Analysis